PENGARUH PEMBERIAN PAKAN ALAMI YANG BERBEDA TERHADAP PERTUMBUHAN LARVA IKAN LELE DUMBO (Clarias gariepinus) - Azis - Hamzah; Ricky Febrinaldy Simanjuntak (Jurnal Akuakultur Rawa Indonesia, 2019)
The purpose of this research was to determine the growth and survival rate occurs in the catfish larvae after being given a different kind of natural feed. This research uses 4 treatments and 3 repetitions. The fish test is used the catfish larvae 4 days old. Natural feed is include Tubifex sp. Moina sp, egg yolk and Commercial feed as fodder for control. The feeding is done 3 times a day in adlibitum. Parameters measured were weight and length growth, survival rate as well as several water quality parameters. The data have been obtained during the study, then analyzed statistically. The results of this research showed the highest weight growth of catfish in a row is the A of (0.166±0.015 gr) and treatment B (0.159±0.015 gr) further treatment C (0.143±0.015 gr) and then treatment D (control), namely (0.151gr ± 0.015 gr). Average of the highest length growth of a row are on treatment A (27.8±3 mm). Followed by treatment B (26.1±3 mm), further treatment C is (19.4±3 mm) and the lowest length growth in treatment D (Control), (15.9±3 mm). And the highest survival rate of catfish was in treatment A (38.55±13.48%), and treatment B (31.77±13.36%), then treatment C (28.88±13.19%) and the lowest survival rates in treatment D (25.11±13.00%). Keywords: Catfish, Natural Feed, Growth Out